Debunking leadership sayings II: the new broom sweeps clean. (2nd January 2019) - Ellis, Peter; Abbott, Jane
Abstract : When starting a new role as a kidney care manager or leader, it can be tempting to change or overhaul work processes immediately in order to put your mark on the department. In some cases, this might include undoing the work of the previous manager. In this article, Peter Ellis and Jane Abbott explain why this approach may not be the best option for both you and your team